To boil an egg: substrate binding affects critical stability in thermal unfolding of proteins - Hussain, Rohanah; Hughes, Charlotte S.; Jávorfi, Tamás; Siligardi, Giuliano; Williams, Paul; Bonev, Boyan B. (American Chemical Society, 2018)
Thermal unfolding of proteins is used extensively in screening of drug candidates because molecular interactions with ligands and substrates affect strongly protein stability, transition temperature, and cooperativity. We use synchrotron radiation circular dichroism to monitor the thermal evolution of secondary structure in proteins as they approach the melting point and the impact of substrate on their thermal behavior. Using Landau free energy expansion, we quantify transition strength and proximity to a critical point through the relative separation τ+ between the transition temperature Tm and the spinodal T+, obtained from the equation of state. The weakest transition was observed in lysozyme with τ+ = −0.0167 followed by holo albumin with τ+ = −0.0208 with the strongest transition in monomeric apo albumin τ+ = − 0.0242. A structural transition at 45 °C in apo albumin leads to a noncooperative melt with τ+ = −0.00532 and amyloidogenic increase in beta content.